Caracterização do teor de gordura do leite através de medidas ópticas - Paiva, Larissa Silva (2023)
Milk is considered one of the most complete foods in the world, being rich in calcium, phosphorus, sodium, potassium and vitamins. Pasteurized milk can be categorized as whole, semi-skimmed and skimmed, with fat content above 3%, between 0.6% to 2.9% and less than or equal to 0.5%, respectively. With advances in research and technology, routine and laboratory analyze have been improving, with emphasis on optical analyses. This procedure eliminates the need to add reagents, does not harm the sample, provides fast results and high accuracy. In this study, we present two new techniques to classify milk based on fat content, using the reduced scattering coefficient (μs'). To determine this data on the integrating sphere (1), we measure the transmission and reflection of the sample at a specific wavelength, 575.1 nm. We observed a direct relationship between milk fat content and μs', that is, the higher the fat content, the higher the value of μs'. This occurs due to the direct relationship between μs' and the size, geometry and quantity of particles/molecules present in the sample. The technique aims to establish a range of values: μs' f 1.5±0.035 mm-1 for skimmed milk, between 1.5 to 3.1±0.035 mm-1 for semi-skimmed milk and μs' g 3.1± 0.035 mm-1 for whole milk. In practice, we use a phantom with the same characteristics as the milk for stability, avoiding variations over time. In addition, we evaluated the average diameter of fat globules, which varies between 2 and 2.5 μm after homogenization. Using the Spatial Frequency Domain Imaging (SFDI) method, we determined the characteristic values for each type of milk: 0.596±0.529 mm-1 for whole milk, 0.416±0.037 mm-1 for semi-skimmed and 0.301±0.019 mm-1 for skimmed. We define a specific classification range for this method and specify the recipe to produce the phantoms that return the desired values. As for the industrial implementation, we recommend using this technique right after milk standardization, to check if the fat content is as desired.